Performance experiment of ultra high temperature cementing slurry system - Zou, Qiang; Chen, Xu; Zhong, Shiming; Yi, Dan; Liu, Liankai (Frontiers in Materials, 2024)
Introduction: The escalating pursuit of oil and gas reserves in China has led to increasingly deep and ultra-deep well drilling, encountering extreme temperatures that challenge the heat resistance capabilities of cement slurries. This study addresses the critical need for high-performance cement slurries capable of withstanding ultra-high temperatures during drilling and completion operations. Methods: A novel ultrahigh temperature conventional density (UHTE) cement slurry was formulated by incorporating high-temperature-resistant additives, namely DRF-1S and DRH-2L. An indoor testing framework was established to assess the slurry’s performance across various parameters: Evaluating the slurry’s ability to maintain uniform consistency over time. Measuring the amount of free water separated from the slurry under simulated downhole conditions. Assessing the slurry’s transition from fluid to solid state over time. Determining the compressive strength and other mechanical attributes after curing at elevated temperatures. Results: The experimental findings revealed the following: An optimal silica sand dosage of 50% was found to enhance the overall performance of the UHTE cement slurry. The developed UHTE cement system, fortified with DRF-1S and DRH-2L, demonstrated effective functionality within a temperature range of 180°C to 210°C, representing a significant advancement in high-temperature resistance. The slurry maintained API water loss below 100 mL, ensuring minimal fluid loss during placement. Adjusted thickening time allowed for adequate pumping and placement without premature setting. Settlement stability was maintained below 0.04 g/cm3, indicating excellent homogeneity and stability. Incorporation of the anti-decay material DRB-3S ensured a 28-day compressive strength exceeding 50 MPa at 210°C, signifying robust structural integrity under extreme thermal conditions. Discussion: This research provides a robust foundation for the practical application of UHTE cementing technology in ultra-high temperature environments. The successful development of the UHTE cement slurry system, characterized by its superior temperature resistance, controlled water loss, optimized thickening behavior, and exceptional mechanical properties, paves the way for field trials and further enhancements. Future work will involve testing the effectiveness of the new additive combination under actual downhole conditions and refining the formulation to develop an even more advanced UHTE cementing additive. These advancements will contribute to enhanced wellbore integrity, improved drilling efficiency, and increased safety in deep and ultra-deep oil and gas exploration endeavors in China.